Clinical benefits of shock index and modified shock index in pulmonary embolism for 30-day mortality prognosis (Annals of Medical Research, 2021)
Aim: It was evaluating the shock index and the modified shock index, which are strongly correlated with the severity of the shock. Determining the risk analysis in terms of early mortality of patients diagnosed with pulmonary thromboembolism (PE) in order to specify treatment options and prognosis. Therefore, it is important to determine the severity of pulmonary embolism correctly. The available algorithms, such as the pulmonary embolism severity index, provide a prediction of the patients according to clinical findings. These algorithms score abnormal vital signs, medical findings, age, and comorbid diseases. However, vital signs in normal physiological limits cause errors in determining the severity of the disease. In this case, the problem is a lack of correlation between the severity of the disease and vital signs. Consequently, we need a more reliable parameter. In our study, we searched for a parameter that can be calculated easily in a dynamic manner, and which is not affected by normalized vital signs. We attempted to find a parameter that could indicate the severity of the disease. Therefore, we evaluated the shock index and the modified shock index, which are strongly correlated with the severity of the shock.Material and Methods: Patients diagnosed with pulmonary embolism were screened retrospectively between January 2012 and December 2017. A total of 99 patients whose pulmonary embolism was confirmed by angio-thoracic tomography were included in the study. Heart rate, systolic and diastolic blood pressure were measured in these patients. Mean arterial pressure, shock index and the modified shock index were also calculated. The values showing the severity of the disease were evaluated.Result When all the parameters were examined, the predictive power of deaths within 30 days was significant at differing degrees (p0.05). In ROC analysis, shock index was the most prominent parameter with its clinical utility and sensitivity. This was followed by pulse count and modified shock index, which are other valuable parameters.Conclusion: At the time of admission to the emergency department, we found that the shock index could be easily calculated with vital signs and display a better correlation with the severity of the disease. Although systolic-diastolic blood pressure, pulse rate and mean arterial pressures calculated in pulmonary embolism are within physiological limits, the shock index shows particularly better correlation and sensitivity of the severity of the disease.Keywords: Pulmonary embolism; shock index; modified shock index.